Supporting and measuring current and future educators' preparedness to facilitate wellbeing of displaced children in schools - Sklad, Marcin (Frontiers in Education, 2023)
Immigrant and refugee children face multiple challenges in accessing education. To help facilitate the educational success and well-being of these children, it is important for teachers to have self-efficacy in creating a supportive learning environment for them. Based on a set of highly interconnected competences identified through a literature review and empirical research, the study developed a measurement instrument to assess teachers' generalized perceived self-efficacy in the domain of working with refugee children: the Newcomer’s Teacher’s Self-Efficacy (NTSE) scale. The scale was tested for validity and internal consistency with 154 practicing and prospective teachers enrolled at three different teacher education institutions in Belgium and the Netherlands, 42 of whom also underwent newcomer education courses. The study examined the factorizability, reliability, and validity of the NTSE scale and showed that the scale is reliable (α=.97) and has good convergent and criterion validity. Results also demonstrated that participation in a study module for newcomer educators corresponded with an increase in partakers’ NTSE scores, and the extent of the module was related to the degree of increase. The proposed scale performed well in the context where it was tested, but further international research is needed to determine its generalizability to different countries and time frames.